Development and Validation of Interactive Computer-Based Learning Module in English - Cortez, Regine P.; Lim, Rich Paulo S. (Akademika, 2025)
This study focused on the development and validation of an interactive computer-based learning module designed for Grade 8 English under the K to 12 curriculum. The module was created following a Research and Development design and evaluated using an experimental approach. Participants were selected from heterogeneous sections of a secondary public school in the Division of Mabalacat City. The experimental group utilized the interactive module, while the control group followed the traditional discussion method. Findings revealed that students who used the interactive module outperformed those taught using traditional methods. Expert validators in both English and Information Technology provided positive evaluations of the module’s content and design. These results demonstrate the module’s effectiveness in enhancing students' academic performance. This study underscores the potential of interactive computer-based modules as valuable tools in fostering 21st-century skills and adapting to evolving educational platforms.